The Preservation of the Javanese Language in the Special Region of Yogyakarta - Wening Udasmoro; J. Susetyo Edy Yuwono; Sulistyowati Sulistyowati; Aprillia Firmonasari; Wulan Tri Astuti; B.R. Suryo Baskoro (Indonesian Journal of Geography, 2023)
The purpose of this study is to map the vulnerable Javanese language in the Special Region of Yogyakarta, namely in the City of Yogyakarta and in the regencies of Sleman, Gunungkidul, Kulon Progo, and Bantul. Furthermore, it seeks to understand the role of different agents in preserving the Javanese language in those areas. Due to the dominating use of Indonesian language, the Javanese language has decreased in usage in various modes of communication in schools especially Jawa krama (medium-register variety). Making this language vulnerability mapping is important to locate in the context of the region, the language vulnerability that occurs more than other regions. This mapping can be used by the policy makers to strengthen the Javanese language used in the regions. A geographic information system was used to map the language's vulnerability in this region. The findings of this research are, first, there is an even distribution of the level of language vulnerability throughout the region, especially in the declining usage of Jawa krama. Second, schools no longer serve as agents in the preservation of the usage and competence of the Javanese language, especially Jawa krama. Third, family and social environments still hold potential for the preservation of the Javanese language, although mostly for Jawa ngoko.